LEGAL PROCEDURE OF TAX COLLECTION BY FORCING LETTER IN THE EFFORT TO SETTLEMENT OF TAX ARREARS BASED ON LAW NUMBER 19 OF 2000 - Cindy Pratiwi; Herman Silaban; Nanda Syahfitri; Shely Winata; ramdanita rumatiga; Arzetti Syahrani Putri I; Silvia Mahdalena Tanjung; Dany Try Hutama Hutabarat (DE'RECHTSSTAAT, 2022)
Tax collection is a series of actions so that the tax insurer pays off tax debts and tax collection costs by admonishing or warning, carrying out instant and simultaneous collections, notifying forced letters, proposing prevention, carrying out confiscations, carrying out hostages, selling confiscated goods. In accordance with the tax system adopted by Indonesia, the Directorate General of Taxes functions as a supervisory agency or implementation of tax obligations. In carrying out this guidance and supervision function, it is carried out through research, examination of tax assessments and collections. To conduct this research, it is carried out by using a normative approach, namely by examining the data on legal materials in the form of Law Number 19 of 2000 concerning Tax Collection by Forced Letters. In Indonesia, the implementation of tax collection with a forced letter based on law number 19 of 2000 which is carried out at the tax service office is not an arbitrary act but is based on a strong legal basis. The implementation of tax collection by force letter is a form of execution without a judge's regulation (which is the authority of the tax authorities) which is usually called direct execution. In the case of tax collection, the forced letter is notified by the tax bailiff with a statement and submission of a copy of the tax letter to the tax guarantor.